2016
DOI: 10.1016/j.jmgm.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenomics knowledgebase and systems pharmacology for hallucinogen target identification—Salvinorin A as a case study

Abstract: Drug abuse is a serious problem worldwide. Recently, hallucinogens have been reported as a potential preventative and auxiliary therapy for substance abuse. However, the use of hallucinogens as a drug abuse treatment has potential risks, as the fundamental mechanisms of hallucinogens are not clear. So far, no scientific database is available for the mechanism research of hallucinogens. We constructed a hallucinogen-specific chemogenomics database by collecting chemicals, protein targets and pathways closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 74 publications
0
19
1
Order By: Relevance
“…Moreover, salvinorin A was reported to have significant affinity for the dopamine D2 receptor [36], which is in contrast to a previous report [5]. Computational studies revealed that not only κ opioid receptor, but also muscarinic acetylcholine receptor 2, cannabinoid CB1 and CB2 receptors, and the aforementioned D2 receptor, may represent potential molecular targets for salvinorin A [37]. Given the above, the differential effects of salvinorin A and standard κ-opioid receptor agonists on seizure susceptibility may result from the fact that the mechanism of action of salvinorin A may be more complex than was thought and is not limited to the activation of the κ-opioid receptors.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, salvinorin A was reported to have significant affinity for the dopamine D2 receptor [36], which is in contrast to a previous report [5]. Computational studies revealed that not only κ opioid receptor, but also muscarinic acetylcholine receptor 2, cannabinoid CB1 and CB2 receptors, and the aforementioned D2 receptor, may represent potential molecular targets for salvinorin A [37]. Given the above, the differential effects of salvinorin A and standard κ-opioid receptor agonists on seizure susceptibility may result from the fact that the mechanism of action of salvinorin A may be more complex than was thought and is not limited to the activation of the κ-opioid receptors.…”
Section: Discussioncontrasting
confidence: 58%
“…Hallucinogen-specific chemogenomics knowledgebase and systems pharmacology analysis We constructed a hallucinogen-specific chemogenomics database [51] that can be used for target, off-target, additional identification, and systems pharmacology analysis of small molecules and their potential targets. Several in-house chemoinformatics tools were utilized, including TargetHunter, HTDocking, and the blood-brain barrier (BBB) predictor [52,53].…”
Section: Simulationsmentioning
confidence: 99%
“…We have constructed a cardiovascular disease (CVD)-specific chemogenomics database [19] that can be used for target/offtarget (or additional) identification and network system pharmacology analysis of small molecules and their potential targets. Several in-house chemoinformatics tools were also used, including TargetHunter, HTDocking, Blood−Brain Barrier (BBB) Predictor (developed by Xie's laboratory, Pittsburgh, PA, USA), etc [20][21][22][23][24][25][26] . CVDPlatform (www.cbligand.org/CVD) archived 984 CVD-related target proteins, 924 approved CVD drugs in clinical trials, 2080 active chemical compounds associated with the therapeutic targets of CVD, 276 cardiovascularrelated pathways, and 350 765 references.…”
Section: V D P L a T F O R M -C A R D I Ova S C U L A R D I S E A Smentioning
confidence: 99%